Challenges and Opportunities in Subnational Public-Private Partnerships in the Philippines - Adoracion M. Navarro (Philippine Institute for Development Studies (PIDS), 2024)
If designed and implemented well, public-private partnership (PPP) projects can fill the gaps in the public provision of infrastructure facilities and social services at the subnational level. The more than three decades of implementing subnational PPPs in the Philippines brought to the fore many challenges, partly due to capacity gaps at the subnational level and the fragmentation in the previous legal frameworks. The fragmentation was characterized by varying and inconsistent local legislative council ordinances on PPPs and joint ventures in the case of local government units and the nationally designed joint venture guidelines in the case of water districts. The policy environment has evolved from a fragmented one to having a legal framework that unifies the various policy approaches of subnational entities. Going forward, the new PPP Code can help subnational government entities be more judicious in entering into new PPP contracts. However, some of the ongoing and newly awarded contracts have remaining issues that will still have to be resolved. One possible solution is contract redesign or amendment when the existing contract is burdensome to the end-users or has the potential to make the end-users unnecessarily bear a huge part of project performance risks. This is permitted under Section 19 of the new PPP Code. Moreover, execution level policymaking should continue, such as the updating of joint memorandum circulars, the revision of manuals and guidelines, the updating of PPP Governing Board policies, and new policies for maximizing commercial value capture or land value capture. To address knowledge and capacity gaps, new technical assistance support for capacity building must be put together. A community of practice must also be supported. Lastly, the promotion of subnational PPPs in sectors where the PPP program can be expanded should also be pursued.
Keywords: 330; subnational public-private partnerships; PPP Code; PPP policy framework; PPP pipeline; contract design; regulation by contract